Laser-Induced Thermal Therapy in the Management of Low-Grade Gliomas: A Narrative Review - Ibrahim Omar hamed Dalabeh; Hossam Salameh; Yasmin Dahabreh; Abdallah Ali suleiman Al-Zayadneh; Mehreen Amir; Ayman Haitham Khaled; Malak A. Hassan; Azad Jehad Makableh; Mohammad Omar hamed Dalabeh (The Journal of Medicine, Law & Public Health)
Background: